Revision of the Fijian Chimarra (Trichoptera, Philopotamidae) with description of 24 new species - Johanson, Kjell Arne; Oláh, János (Zootaxa, 2012)
The philopotamid genus Chimarra (Trichoptera) of Fiji is revised. The previously described species Chimarra nervosa(Brauer, 1867) is considered a nomen dubium. Chimarra indigota Mosely, 1941, is synonymized with Chimarra manniBanks, 1924. The following 24 new Chimarra species are described: C. vanuensis, C. macuatensis, C. schlingeri, C. nath-ani, C. braueri, C. vitiensis, C. karoyanitensis, C. tokotaai, C. vuda, C. naitasirensis, C. veisarensis, C. fijiana, C. abacen-sis, C. cakaudrovensis, C. cartwrighti, C. kimminsi, C. kadavuensis, C. lavensis, C. devoensis, C. helomyzida, C. tipulida,C. psychodida, C. levuensis, and C. malickyi. Chimarra signata Banks, 1936, C. manni Banks, 1924, and C. obscurella Banks, 1924, are re-described based on type material.